Spiritual Awakening through Tantra: A Utopian Approach to Aldous Huxley’s Island - Paudyal, Ganga Ram (The Outlook: Journal of English Studies, 2025)
This paper explores Aldous Huxley’s novel Island in which tantra is depicted to liberate people of the island Pala and to make the island a utopia. The issue concerning how the attempts are made to reflect tantra in the novel as a transformative force to create Pala as an idyllic island. The objective of this paper is to find out how people are trained in Pala and how Will Farnaby undergoes transformation avoiding his vested interest. The paper also aims to find out the role of tantra for maintaining unity, peace and solidarity among people in Pala and attempts are made to make it an ideal state. Adoption of tantra, use of moksha-medicine and practice of maithuna (the yoga of love) reflect the way spiritual enlightenment has been emphasized to make the island unique. The tantric principles are used to transcend ego, to achieve a higher sense of consciousness and unity with the world and supreme entity. Adopting a qualitative method of study, the paper reviews some articles and books on Huxley’s work as secondary sources. The novel as a primary source has provided data and information about tantra and its role to transform and liberate the people of Pala and establish a utopian vision. To address this issue, the paper has employed utopia as ideal theory propounded by Thomas More. The finding of this study indicates that tantra as a transformative as well as a liberating force in Pala and it is used to make it a paradise island or an ideal place. Tantra can also be applied as a transformative factor to create idyllic societies as it has been adopted in the novel to make it a utopia.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />